Are Currency Crises Predictable? - Valdes, Rodrigo (IMF Working Papers; Working Paper ;, 1997)
This paper studies whether exchange rate expectations and overvaluations are predictors of currency crises. The results suggest that overvaluation has predictive power in explaining crises. However, although expected depreciation obtained from survey data partially takes different measures of exchange rate misalignment into consideration, expectations fail to anticipate currency crises.